Comparative analysis of the complete mitogenomes of Camellia sinensis var. sinensis and C. sinensis var. assamica provide insights into evolution and phylogeny relationship - Li, Li; Li, Xiangru; Liu, Yun; Li, Junda; Zhen, Xiaoyun; Huang, Yu; Ye, Jianghua; Fan, Li (Frontiers in Plant Science, 2024)
Among cultivated tea plants (Camellia sinensis), only four mitogenomes for C. sinensis var. assamica (CSA) have been reported so far but none for C. sinensis var. sinensis (CSS). Here, two mitogenomes of CSS (CSSDHP and CSSRG) have been sequenced and assembled using a combination of Illumina and Nanopore data for the first time. Comparison between CSS and CSA mitogenomes revealed a huge heterogeneity. The number of the repetitive sequences was proportional to the mitogenome size and the repetitive sequences dominated the intracellular gene transfer segments (accounting for 88.7%- 92.8% of the total length). Predictive RNA editing analysis revealed that there might be significant editing in NADH dehydrogenase subunit transcripts. Codon preference analysis showed a tendency to favor A/T bases and T was used more frequently at the third base of the codon. ENc plots analysis showed that the natural selection play an important role in shaping the codon usage bias, and Ka/Ks ratios analysis indicated Nad1 and Sdh3 genes may have undergone positive selection. Further, phylogenetic analysis shows that six C. sinensis clustered together, with the CSA and CSS forming two distinct branches, suggesting two different evolutionary pathway. Altogether, this investigation provided an insight into evolution and phylogeny relationship of C. sinensis mitogenome, thereby enhancing comprehension of the evolutionary patterns within C. sinensis species.